131 Designing an educational app for patients with heart failure. (4th June 2021) - Singhal, Arvind; Tandon, Juhi; Ringrose, Tim; Cowie, Martin
Abstract : Introduction: Patient education and engagement is a priority for heart failure (HF) care but given low health literacy and high anxiety around diagnosis in HF, consultations and written materials may not be the optimum medium for this, particularly with the rise in remote consultations following the Covid-19 pandemic. Mobile applications (Apps) have shown early promise as patient education tools. In particular, 'Avatar'-based Apps, where a virtual, interactive 3D character serves as a teacher, have shown potential in other conditions such as ischaemic heart disease and rheumatoid arthritis. Methods: A moderated, structured focus group of 8 HF patients and one patient carer was held to explore their experiences with patient education and identify areas in which HF education and knowledge of self-care was lacking. All participants shared their thoughts during moderated discussion, and recurring themes were identified. Participants then developed a 'curriculum' of topics that they considered most important in an educational App, with input from the HF team. Results: Key themes that emerged from patients' prior experience of patient education included feelings of being overwhelmed and isolated during the initial diagnosis of HF, the importance of a trusted medium for accessing health information (and fear of misinformation), and 'a picture says a thousand words' – visual information was easier to absorb than text. The educational curriculum developed by participants prioritised the following areas: impact on lifestyle, medical management (including the importance of HF medicines), lifestyle changes and care planning, and self-management (including monitoring for signs of deterioration). A prototype App was developed in conjunction with Cognitant Group, using an Avatar ( figure 1 ). The Avatar was designed to be a patient expert in HF, aged ~65 years old. A living room setting was picked for the content for viewers to feel more relaxed. For Avatar movements to seem natural, voice and movements were recorded and synchronised using motion-capture technology. The first module entitled 'Living with heart failure' outlines of the following topics: explaining HF and the typical patient journey, the purpose of HF medications, lifestyle advice (including exercise and healthy eating, smoking and alcohol, sex and relationships), self-monitoring of HF symptoms, when to call for help and signposts to trusted HF educational resources. Acceptability of the App is currently being evaluated in the HF cohort at this specialist centre. Conclusions: Avatar-based Apps may be a useful tool in patient education in HF when co-designed with patients. Further research will evaluate the acceptability of such an App to a cohort of patients in a specialist HF centre. Conflict of Interest: Laboratoires Servier provided funding for the development of the App. Dr Singhal's salary is funded by a fellowship from Abbott.